Cost comparisons of five leading brands of the antihypertensive drug, Telmisartan, available in an Indian city - Rajadnya, Vikram A.; Bedi, Sheena R. (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Antihypertensive drugs have to be taken lifelong, after initiation of the treatment. Price variation can lead to huge economic burden on the patients of hypertension, especially when cost considerations are not undertaken by the prescribing physician . This study was undertaken to compare the annual cost , to the patient , of five different most commonly prescribed brands of Telmisartan 40 mg, in Kolhapur city. Methods: Authors purchased a strip of 10 tablets each of the five leading brands in one city, Kolhapur, India, of Telmisartan 40 milligram. The prices of the strip of 10 tablets of each of the five selected brands were compared. In turn the annual cost of each of these five, was compared directly as well as using percentages. The data was collected, analysed and presented. Results: The data of the cost of the preparations of five different brands of a single antihypertensive drug, Temisartan 40 milligram shows that the annual cost of the costliest among the three brands of this drug is almost three times , that of the cheapest brand, or in other words almost 300 percent that of the cheapest brand. Conclusions: the cost variation amongst the five brands was considerable. India being a country with a major chunk of the population being very price sensitive, the prescribing physician must select the brand carefully. The most costly preparation of Temisartan can significantly add to the burden on the patient’s annual budget. Thus, Pharmacoeconomics must take an important place while prescribing medicines, especially in a country like India.